Religion and Politics in the Light of Mimetic Theory - Romejko, Adam (Poznańskie Studia Slawistyczne, 2016)
René Girard, the French-American literary critic and anthropologist, gives us the mimetic theory, which turns out to be an interesting tool for the interpretation of human relationships. It is based on the analysis of works of the world literature, including myths and the Bible. As a part of human nature mimesis leads to a conflict and at the same time it saves through a scapegoat. This is reflected in religious rituals, which are the first human institutions leading directly to a political institution – to the monarchy. The reality of the victim is firmly anchored in human culture, including the contemporary, despite the fact that it does not see this. This applies to all circles of civilization, including the West.